Analisis Random Walk Saham Unilever Selama Tahun 2020-2022 - Andri Faisal (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2022)
The decline in Unilever's share price is quite worrying during 2021-2022. This decline can be worrying especially as this company is a very good company . Whereas previously this stock had a good value. The ups and downs become a phenomenon to explain what happened. After collecting data for the last two years from the closing price of Unilever shares, the results show that the data is not stationary. To overcome using the difference in seasonality. In the first differencing (first difference) the value of the data becomes stationary. With the stationary, the data can be predicted. In the non-random test, it can be seen that the time series data is non-random. the results of the two tests show that there is no random walk in the Unilever time series data, meaning that the data on closing the UVNR stock price can be predicted. The existence of a random walk also indicates an inefficient market.